Musculoskeletal ultrasound imaging of the plantar forefoot in patients with rheumatoid arthritis: inter-observer agreement between a podiatrist and a radiologist - Bowen Catherine J; Dewbury Keith; Sampson Madeline; Sawyer Sally; Burridge Jane; Edwards Christopher J; Arden Nigel K (Journal of Foot and Ankle Research, 2008)
Abstract Background The use of musculoskeletal ultrasound (MSUS) in the diagnosis and management of foot and ankle musculoskeletal pathology is increasing. Due to the wide use of MSUS and the depth and breadth of training required new proposals advocate tailored learning of the technique to discrete fields of practice. The aims of the study were to evaluate the inter-observer agreement between a MSUS radiologist and a podiatrist, who had completed basic skills training in MSUS, in the MSUS assessment of the forefoot of patients with Rheumatoid Arthritis. Methods A consecutive sample of thirty-two patients with rheumatoid arthritis was assessed for presence of synovitis, erosions and bursitis within the forefoot using MSUS. All MSUS assessments were performed independently on the same day by a podiatrist and one of two Consultant Radiologists experienced in MSUS. Results Moderate agreement on image acquisition and interpretation was achieved for bursitis (kappa 0.522; p < 0.01) and erosions (kappa 0.636; p < 0.01) and fair agreement for synovitis (kappa 0.216; p < 0.05) during the primary assessments. Following a further training session, substantial agreement (kappa 0.702) between the two investigators was recorded. The sensitivity of the podiatrist using MSUS was 82.4% for detection of bursitis, 83.0% for detection of erosion and 84.0% for detection of synovitis. Specificity of the podiatrist using MSUS was 88.9% for detection of bursitis, 80.7% for detection of erosion and 35.9% for detection of synovitis. Conclusion This study demonstrated good inter-observer agreement between a podiatrist and radiologist on MSUS assessment of the forefoot, particularly for bursitis and erosions, in patients with rheumatoid arthritis. There is scope to further evaluate and consider the role of podiatrists in the MSUS imaging of the foot following appropriate training and also in the development of reliable protocols for MSUS assessment of the foot.